The level of evaluation of the educational counselors ’performance as a predictor of their level of satisfaction with their evaluation (Journal Of Educational and Psychological Researches, 2022)
The current research aims to reveal the level of satisfaction of the mentors with the evaluation of their performance according to gender (male - female) and to formulate the predictive equation for the level of performance (dependent variable) from knowing the level of satisfaction with the evaluation (independent variable). (16 paragraphs) contains alternatives to the answer that measures the level of satisfaction (weak, medium, and high) (1,2,3), that is, with a hypothetical average of (32). It consisted of 100 educational counselors consisting of 45 males and 55 females, the results of the research concluded that the level of satisfaction with performance is below the mean when compared with the hypothetical average of the scale of satisfaction with evaluation, that the gender variable does not affect the level of satisfaction with the evaluation.